Epigenetic mechanisms of particulate matter exposure: air pollution and hazards on human health - Gavito-Covarrubias, Dulcemaría; Ramírez-Díaz, Ivonne; Guzmán-Linares, Josué; Limón, Ilhuicamina Daniel; Manuel-Sánchez, Dulce María; Molina-Herrera, Alejandro; Coral-García, Miguel Ángel; Anastasio, Estela; Anaya-Hernández, Arely; López-Salazar, Primavera; Juárez-Díaz, Gabriel; Martínez-Juárez, Javier; et al. (Frontiers in Genetics, 2024)
Environmental pollution nowadays has not only a direct correlation with human health changes but a direct social impact. Epidemiological studies have evidenced the increased damage to human health on a daily basis because of damage to the ecological niche. Rapid urban growth and industrialized societies importantly compromise air quality, which can be assessed by a notable accumulation of air pollutants in both the gas and the particle phases. Of them, particulate matter (PM) represents a highly complex mixture of organic and inorganic compounds of the most variable size, composition, and origin. PM being one of the most complex environmental pollutants, its accumulation also varies in a temporal and spatial manner, which challenges current analytical techniques used to investigate PM interactions. Nevertheless, the characterization of the chemical composition of PM is a reliable indicator of the composition of the atmosphere, the quality of breathed air in urbanized societies, industrial zones and consequently gives support for pertinent measures to avoid serious health damage. Epigenomic damage is one of the most promising biological mechanisms of air pollution-derived carcinogenesis. Therefore, this review aims to highlight the implication of PM exposure in diverse molecular mechanisms driving human diseases by altered epigenetic regulation. The presented findings in the context of pan-organic cancer, fibrosis, neurodegeneration and metabolic diseases may provide valuable insights into the toxicity effects of PM components at the epigenomic level and may serve as biomarkers of early detection for novel targeted therapies.